REDESIGN OF DRAINAGE CHANNELS FOR HIGH RAINFALL IN THE PECANGAAN DISTRICT JEPARA REGENCY (CASE STUDY OF NGELING VILLAGE) (Science and Technology (SciTech), 2023)
On Jl. Pecangaan – Bugel, Ngeling Village, Pecangaan District, Jepara Regency, found drainage and flooding problems that often occur along the main road during the rainy season. From the problems found there is no drainage channel due to housing construction that does not pay attention to the drainage function and can result in damage to road construction. This final project analyzes drainage channels with the aim of knowing alternative flood management. The results of hydrological planning calculations will be used as a basis for hydraulic analysis, rainfall calculations will use the isohyet method. The hydraulic analysis was carried out with the help of the HEC-RAS and EPA SWMM assistance programs. Based on the analysis of existing conditions, it is known that water inundation occurs because the channel capacity is unable to accommodate flood discharge, such as channel dimensions that are not suitable, so new planning is needed. The results of the HEC – RAS Software analysis are more effective as an alternative to handling flood problems in accordance with the conditions of Jl. Pecangaan – Bugel Ngeling Village, Pecangaan District, Jepara Regency with a new drainage channel plan with dimensions b = 1.5 m and h = 1.5 m. Keywords : HEC-RAS, EPA SWMM, and Drainage.